(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Apulicallis trojanae, gen. n., sp. n., (Homoptera Aphididae) is described from ltaly, where it lives on the Macedonian Oak, Quercus trojana Webb. Accounts are given of its morphology (alate viviparous female, fundatrix, alatoid nymph, embryo, male and ovipara), taxonomy, distribution and life cycle.